Genomic and chemical insights into a human lectin-binding extracellular polysaccharides from Parageobacillus toebii strain H-70 - Diana Ghevondyan; Armine Margaryan; Fabrizio Chiodo; Yvette van Kooyk; Ilaria Finore; Annarita Poli; Hovik Panosyan (PLoS ONE, 2026)
Extracellular polysaccharides (EPSs) from thermophilic bacteria are promising biopolymers due to their stability and structural variability. This study aimed to characterize the genomic and chemical features of EPS produced by Parageobacillus toebii strain H-70 isolated from a geothermal spring in Armenia. EPS from strain H-70 was produced in sucrose and glucose based medium and analyzed chemically by TLC, HPAEC-PAD, GC-MS, and NMR. Protein, uronic acid, and nucleic acid contents were quantified by spectrophotometric methods. Molasses, an inexpensive byproduct of sugar production, was used as the carbon source too. Whole-genome sequencing, comparative phylogenomics, and genome mining were performed to identify biosynthetic gene clusters, carbohydrate-active enzymes (CAZymes), and regulatory components associated with EPS metabolism. Strain H-70 yielded 37.9 mg/L EPS (0.10 g/g dry cell weight) after 72 h cultivation at 55 °C and pH 7.0 with sucrose as sole carbon source. The EPS was a heteropolysaccharide composed of rhamnose, glucose, galactose, and mannose, along with proteins (15.04%), uronic acids (4.22%), and nucleic acids (4.88%). The EPS yield obtained with glucose as the sole carbon source was 10.5 mg/L, whereas molasses supplementation resulted in a yield of 14.5 mg/L. The draft genome (~3.2 Mb, 42% G + C, 98.9% ANI with P. toebii DSM 14590) encoded five Wzy-dependent EPS gene clusters with glycosyltransferases, transporters, and regulators. The genome also carried diverse CAZymes (GH, GT, CE, CBM, AA families) and modification enzymes (e.g., CsaB, acetyltransferases), indicating structural and functional variability of the polymer. In addition, the binding to human C-type lectins (carbohydrate-binding proteins involved in innate and adaptive immune-responses) has been studied by solid-phase assay. This study provides the first comprehensive characterization of EPS from P. toebii H-70, integrating genomic and chemical insights. The binding to human C-type lectins offers future EPSs biomedical applications especially in as immune-modulators.